(untitled) (Research, Society and Development, 2021)
The aim of the present study was to understand the importance of Sports Dentistry for the athlete’s health, to verify the most prevalent oral diseases in high-performance athletes and to identify the influence of oral diseases on the athlete’s performance. Literature searches were carried out in the following electronic databases: Virtual Health Library, SciELO, Google Scholar, Pubmed and Portal de Periódicos Capes / MEC. It was observed that oral care goes beyond the indication of the use of mouthguards. The dentist acts in the prevention and intervention of harmful factors such as caries disease, temporomandibular disorder, periodontal disease, malocclusion, deleterious habits, dental erosion, in addition to dental and orofacial trauma caused by the impact on contact sports. Attention is even given to the prescription of medications, so that there is no risk of a positive result in doping control. One of the concerns in treating oral diseases, is due to the fact of the systemic repercussions, as they can impair the capacity of muscle regeneration, generate respiratory problems and cardiovascular complications. In addition to compromising masticatory efficiency, speech, favoring dental trauma, and also decreasing athletes’ willingness and ability to concentrate in cases of pain. There is a need for further studies on the subject and for the dissemination in the sports environment of the importance of oral health for the maintenance of systemic health and, consequently, improvement of the athletes’ sports performance.